Frank M. Johnson papers - Johnson, Frank M. (Frank Minis), 1918-1999.
Correspondence, memoranda, agenda and minutes of meetings, reports, case files, opinions, orders, briefs, writs, motions, petitions, depositions, transcripts, notes, clippings, printed matter, and other papers documenting Johnson's career as a federal judge and his involvement in professional activities. Documents his service as a judge on the U.S. District Court for the Middle District of Alabama (1955-1979), the Temporary Emergency Court of Appeals of the U.S. (1972-1982), and the U.S. Court of Appeals, 5th Circuit (1979-1981) and 11th Circuit (1981- ). Also documents his membership on the Advisory Committee on Criminal Rules for the Judicial Conference of the United States. Johnson's cases as district court judge pertain primarily to civil rights for African Americans, the mentally ill, and prison inmates. Significant cases include those relating to the Montgomery, Ala., bus boycott (Browder v. Gayle), the Selma-Montgomery march (Williams v. Wallace), school desegregation (Lee v. Macon County Board of Education), and living conditions in Alabama prisons (Pugh v. Locke and James v. Wallace) and in the state's psychiatric hospitals (Wyatt v. Stickney). Papers from his service on the Temporary Emergency Court of Appeals focus on energy regulations relating to the Emergency Petroleum Allocation Act of 1973. Johnson's files as appellate judge include cases relating to civil rights, constitutional law including search and seizure and constitutional challenges to state statutes, antitrust issues, prisoners' rights, and tax and bankruptcy issues. Also documents his work on the Judicial Council of the 11th Circuit leading to the impeachment of U.S. District Court judge Alcee L. Hastings.
Correspondents include Griffin B. Bell, Harry A. Blackmun, John Robert Brown, Paul W. Bryant, Warren E. Burger, Emanuel Celler, Morris Dees, Ira DeMent, John Doar, John C. Godbold, William Burnett Harvey, Fob James, Vernon E. Jordan, William C. Keady, Clarence M. Kelley, Robert F. Kennedy, Seybourne H. Lynne, Burke Marshall, Walter F. Mondale, Huey P. Newton, Richard T. Rives, Hugh Scott, Edward A. Tamm, Elbert P. Tuttle, Robert E. Varner, and Earl Warren.
Lawyer and judge.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bell, Griffin B., -- 1918-2009 -- Correspondence; Blackmun, Harry A. -- 1908-1999 -- Correspondence; Browder, Aurelia S. -- Trials, litigation, etc; Brown, John Robert, -- 1909- -- Correspondence; Bryant, Paul W. -- Correspondence; Burger, Warren E., -- 1907-1995 -- Correspondence; Celler, Emanuel, -- 1888-1981 -- Correspondence; Dees, Morris -- Correspondence; DeMent, Ira, -- 1931- -- Correspondence; Doar, John, -- 1921- -- Correspondence; Gayle, W. A. -- Trials, litigation, etc; Godbold, John C. -- 1920- -- Correspondence; Harvey, William Burnett, -- 1922-1999 -- Correspondence; Hastings, Alcee L; James, Fob, -- 1934- -- Correspondence; James, Worley -- Trials, litigation, etc; Jordan, Vernon E. -- 1935- -- Correspondence; Keady, William C., -- 1913- -- Correspondence; Kelley, Clarence M. -- Correspondence; Kennedy, Robert F., -- 1925-1968 -- Correspondence; Lee, Anthony T. -- Trials, litigation, etc; Locke, Judson C. -- Trials, litigation, etc; Lynne, Seabourn H. -- 1907- -- Correspondence; Marshall, Burke, -- 1922-2003 -- Correspondence; Mondale, Walter F., -- 1928- -- Correspondence; Newton, Huey P. -- Correspondence; Pugh, Jerry Lee -- Trials, litigation, etc; Rives, Richard T. -- 1895-1992 -- Correspondence; Scott, Hugh, -- 1900-1994 -- Correspondence; Stickney, Stonewall B. -- Trials, litigation, etc; Tamm, Edward A. -- 1906- -- Correspondence; Tuttle, Elbert P. -- 1897- -- Correspondence; Varner, Robert E. -- 1921- -- Correspondence; Wallace, George C. -- 1919-1998 -- Trials, litigation, etc; Warren, Earl, -- 1891-1974 -- Correspondence; Williams, Hosea, -- 1926- -- Trials, litigation, etc; Wyatt, Ricky -- Trials, litigation, etc; Macon County (Ala.) -- Board of Education -- Trials, litigation, etc; United States; United States. -- Court of Appeals (5th Circuit); United States. -- Court of Appeals (11th Circuit); United States. -- Court of Appeals (11th Circuit). -- Judicial Council; United States. -- District Court (Alabama : Middle District); United States. -- Temporary Emergency Court of Appeals; Judicial Conference of the United States. -- Advisory Committee on Criminal Rules; African Americans -- Civil rights; Antitrust law; Appellate courts; Bankruptcy; Civil rights demonstrations -- Alabama; Civil rights; Constitutional law; District courts -- Alabama; Energy policy -- United States; Federal-state controversies; Mentally ill -- Civil rights -- Alabama; Petroleum law and legislation -- United States; Prisoners -- Civil rights; Searches and seizures; Taxation